2001
DOI: 10.1002/1521-3757(20010119)113:2<448::aid-ange448>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Cyano-Bridged 4f-3d Coordination Polymers with a Unique Two-Dimensional Topological Architecture and Unusual Magnetic Behavior

Abstract: 24‐gliedrige Ringe bauen die zweidimensionale Struktur der neuartigen Verbindungen [NdM(bpym)(H2O)4(CN)6]⋅3 H2O (M=Fe (1), Co (2); bpym=2,2′‐Bipyrimidin) auf. Dies sind die ersten zweidimensionalen cyanoverbrückten Verbindungen mit Lanthanoid‐ und Übergangsmetallzentren (siehe Bild). Außer ihren Strukturen wurden auch ihre magnetischen Eigenschaften untersucht.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…There are antiferromagnetically coupled triangular sublattices within the layered Gd 3+ wheel‐cluster network. Such a frustrated spin geometry has ever been inferred to play a crucial role in the field‐induced frequency‐dependent magnetic behaviors of some lanthanide complexes 27. However, with the development in magnetochemistry of lanthanide complexes, this field‐induced relaxation process tends to be explained by the magnetic behavior of an isolated ion, the lifting of the Kramer degeneracy by the applied magnetic field is responsible for this magnetic phenomenon 28.…”
Section: Resultsmentioning
confidence: 99%
“…There are antiferromagnetically coupled triangular sublattices within the layered Gd 3+ wheel‐cluster network. Such a frustrated spin geometry has ever been inferred to play a crucial role in the field‐induced frequency‐dependent magnetic behaviors of some lanthanide complexes 27. However, with the development in magnetochemistry of lanthanide complexes, this field‐induced relaxation process tends to be explained by the magnetic behavior of an isolated ion, the lifting of the Kramer degeneracy by the applied magnetic field is responsible for this magnetic phenomenon 28.…”
Section: Resultsmentioning
confidence: 99%
“…In the very beginning of our research, a DC field dependent slow magnetic relaxation was observed in the Nd III containing 2D coordination polymer. 27 The slow magnetic relaxation was at first attributed to the presence of frustration which is unveiled by the static DC field. 28 This DC field induced slow magnetic relaxation was later found to be rather general in lanthanide containing complexes with or without 3d spin carriers.…”
Section: Survey Of 4f-simsmentioning
confidence: 99%
“…42,43 Also, trivalent Ln III -MOFs can be considered to be promising molecular magnetic materials because they have large magnetic anisotropy and strong spin−orbit coupling except for gadolinium(III)-based MOFs. 44,45 Among the organic linkers used for the construction of Ln-MOFs, rigid polycarboxylates such as furandicarboxylic, 46−49 thiophenedicarboxylic, 50−52 pyridinedicarboxylic, 53−57 isophthalic, 58,59 terephthalic, 60−63 2,6-naphthalenedicarboxylic, 64−67 and trimesic 68−71 acids are of special interest. They have been widely exploited for the synthesis of Ln-MOFs.…”
Section: ■ Introductionmentioning
confidence: 99%